2006
DOI: 10.1002/app.24769
|View full text |Cite
|
Sign up to set email alerts
|

Humidity sensitivity of polypyrrole and polypyrrole/SBA‐15 host–guest composite materials

Abstract: Polypyrrole (PPY) and PPY/SBA-15 hostguest composite materials have been prepared using chemical synthesis route and characterized by XRD, IR, N 2 adsorption-desorption isotherms, and SEM. The humidity sensitive properties (HSP) of this kind of materials have been studied by analyzing the variation curve of impedance as a function of relative humidity. It was found that the PPY/SBA-15 host-guest composites materials exhibit better HSP than that of the corresponding pure PPY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The Brunauer-EmmettTeller surface area and pore volume decreased greatly compared to that of pure SBA-15. 21 These results confirm the successful encapsulation of NiO/ PPy into SBA-15. Figure 5 shows the differential thermal analysis (DTA) and thermogravimetric analysis (TGA) curves of NiO-PPy/SBA-15.…”
supporting
confidence: 87%
“…The Brunauer-EmmettTeller surface area and pore volume decreased greatly compared to that of pure SBA-15. 21 These results confirm the successful encapsulation of NiO/ PPy into SBA-15. Figure 5 shows the differential thermal analysis (DTA) and thermogravimetric analysis (TGA) curves of NiO-PPy/SBA-15.…”
supporting
confidence: 87%
“…Table shows comparison of the humidity sensing properties of Mn/SBA‐15 nanocomposites with other hybrid SBA‐15 materials . It is found that our material possess very high surface area and pore volume due to one step synthesis strategy involved in the preparation of nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…Table II shows comparison of the humidity sensing properties of Mn/SBA-15 nanocomposites with other hybrid SBA-15 materials. [38][39][40][41][42] It is found that our material possess very high surface area and pore volume due to one step synthesis strategy involved in the preparation of nanocomposite. The comparatively enhanced mesoporous properties create abundant pore opportunities for free movement of charged ions, thus causing more than five order of magnitude changes in resistance together with negligible hysteresis in the 11%-92% RH range.…”
Section: March 2015mentioning
confidence: 93%
“…Modification of mesoporous SBA-15 using polypyrrole (PPY) demonstrated this impact as well. When compared to the SBA-15 material, the SBA-15/PPY composite showed a response over a larger range of RH values [34]. Modification of the SBA-15 material using hydrophilic Li + resulted in an impendence change over three orders of magnitude, considerably greater than that of the undoped SBA-15.…”
Section: Sensors For Relative Humiditymentioning
confidence: 99%